Information Transmission in Hierarchies - Simon Schopohl (Bielefeld University, Center for Mathematical Economics (IMW), 2017)
We analyze a game in which players with unique information are arranged in a hierarchy. In the lowest layer each player can decide in each of several rounds either to pass the information to his successor or to hold. While passing generates an immediate payoff according to the value of information, the player can also get an additional reward if he is the last player to pass. Facing this problem while discounting over time determines the player's behavior. Once a successor has collected all information from his workers he starts to play the same game with his successor. We state conditions for different Subgame Perfect Nash Equilibria and analyse the time it takes each hierarchy to centralize the information. This allows us to compare different structures and state which structure centralizes fastest depending on the information distribution and other parameters. We show that the time the centralization takes is mostly affected by the least informed players.
urn:nbn:de:0070-pub-29091428
Keywords: D83; C72; C73; 330; communication network; dynamic network game; hierarchical structure; information transmission